IMF Staff Papers, Volume 50, No. 2 - Flood, Robert (Washington, D.C. : International Monetary Fund, 2003)
This paper examines sources of economic growth in East Asia. The conventional growth-accounting approach to estimating the sources of economic growth requires unrealistically strong assumptions about either competitiveness of factor markets or the form of the underlying aggregate production function. The paper outlines a new approach utilizing nonparametric derivative estimation techniques that does not require imposing these restrictive assumptions. The results for East Asian countries show that output elasticities of capital and labor tend to be different from the income shares of these factors. The paper also explores the compensating potential of private intergenerational transfers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet